Prevalence of dental caries in the primary dentition among under five children (Bangladesh Medical Journal Khulna, 2012)
Dental caries is the most important dental health problem in developing countries. The study aimed to estimate the prevalence of dental caries in primary dentition among under 5 years children. A simple random sampling method was used. Study population was under 5 children attending dental department of Khulna Medical College Hospital from January to June 2010. A total of 672 children were examined. The prevalence of dental caries was 44.34%. Caries prevalence was higher in the boys than the girls and it was statistically significant (P